TEKNIK DAN INSTRUMEN ASESMEN KETERAMPILAN PENDIDIKAN AGAMA ISLAM DI DIKDASMEN DAN PENDIDIKAN TINGGI - Forisma, Andi; Ni'mah, Zulfatun; Sukiman (Jurnal Evaluasi Pendidikan, 2023)
The purpose of this research is to investigate various techniques and instruments for assessing the realm of skills at the primary, secondary, and higher education levels, as well as their implications in learning Islamic religious education.This research method combines library research with descriptive analysis techniques. The source of the data comes from educational assessment books, permendikbud, and other literature relevant to the topic of discussion. According to the findings of this study, the technique of assessing aspects of skills in learning Islamic religious education at the primary, secondary, and higher education levels is both test and non-test assessment.Psychomotor assessment with tests, including performance test techniques consisting of identification tests, simulation tests, picking tests, and paper and pencil tests Meanwhile, psychomotor assessment with non-tests can be accomplished through the use of products, projects, portfolios, anecdotal records, and self-assesment and peer-assessment. Meanwhile, instruments that can be used in psychomotor assessment include checklists, rating scales, and notes.